2000
DOI: 10.1542/peds.106.6.e89
|View full text |Cite
|
Sign up to set email alerts
|

Technical Report: Precautions Regarding the Use of Aerosolized Antibiotics

Abstract: ABSTRACT. In 1998, the Food and Drug Administration (FDA) approved the licensure of tobramycin solution for inhalation (TOBI). Although a number of additional antibiotics, including other aminoglycosides, ␤-lactams, antibiotics in the polymyxin class, and vancomycin, have been administered as aerosols for many years, none are approved by the FDA for administration by inhalation.TOBI was approved by the FDA for the maintenance therapy of patients 6 years or older with cystic fibrosis (CF) who have between 25% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 47 publications
1
24
0
2
Order By: Relevance
“…Aerosolized antibiotics have been studied most extensively in children in the setting of cystic fibrosis. The FDA approval of tobramycin solution for inhalation is only for maintenance therapy in patients with cystic fibrosis known to be colonized with Pseudomonas aeruginosa (76). In two randomized controlled trials, a modest improvement in the forced expiratory volume in 1 min occurred after 24 weeks of therapy with tobramycin solution for inhalation; there were significant decreases in CFU/ml of Pseudomonas aeruginosa in sputum, decreases in hospital admission days, and decreases in numbers of parenteral antibiotic days for treatment of Pseudomonas aeruginosa infections.…”
Section: Specific Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerosolized antibiotics have been studied most extensively in children in the setting of cystic fibrosis. The FDA approval of tobramycin solution for inhalation is only for maintenance therapy in patients with cystic fibrosis known to be colonized with Pseudomonas aeruginosa (76). In two randomized controlled trials, a modest improvement in the forced expiratory volume in 1 min occurred after 24 weeks of therapy with tobramycin solution for inhalation; there were significant decreases in CFU/ml of Pseudomonas aeruginosa in sputum, decreases in hospital admission days, and decreases in numbers of parenteral antibiotic days for treatment of Pseudomonas aeruginosa infections.…”
Section: Specific Treatmentmentioning
confidence: 99%
“…No ototoxicity or nephrotoxicity has been associated with the use of inhaled aminoglycosides, although many of those studies excluded children with serum creatinine levels greater than 2. The potential disadvantages of use include bronchospasm, increased MICs of the targeted organism, increased isolation of Candida and Aspergillus species from sputum, nebulization of microorganisms, and antibiotic contamination of the environment (76).…”
Section: Specific Treatmentmentioning
confidence: 99%
“…Co-nebulizing several antibiotics is difficult because some combinations of antibiotic solutions can form precipitates (13). Finally, nebulization disperses antibiotics into the ambient air and generates antibiotic resistance among ubiquitous bacteria (14). The ideal vehicle for inhalational delivery of antibiotics should deliver the effective drug, provide a high FPF, allow for simultaneous delivery of multiple potentially chemically incompatible antibiotics, limit the contamination of ambient air, and be easy to use.…”
Section: Introductionmentioning
confidence: 99%
“…In CF patients P. aeruginosa often develops resistance if treated with a single antibiotic (such as tobramycin, ceftazidime, or ciprofloxacin), and many clinicians use two or more agents of different classes simultaneously to prevent this (14,(17)(18)(19)(20)(21). Coencapsulating the two compounds in the same particles would assure their co-deposition in the airway at the intended doses.…”
Section: Introductionmentioning
confidence: 99%
“…The Austrian study was in fact very encouraging but the same group reported that longterm gentamicin inhalation in CF children was associated with reversible raised urinary Nacetyl-beta-D-glucosaminidase (NAG) activity, consistent with subtle subclinical renal tubular damage (Ring et al, 1998). Tobramycin and amikacin however have lower renal toxicity than gentamicin and long-term use of high doses of inhaled tobramycin (TOBI) are now considered safe (Prober et al, 2000). There are several theoretical arguments that make long-term inhaled prophylactic antibiotic therapy attractive (Lebecque et al, 2008).…”
Section: Challenge 1: Postpone Chronic Colonisation By Pseudomonas Aementioning
confidence: 99%